Characterization of burnout in doctors at the Provincial Hospital of Portoviejo, Manabí, Ecuador, during the pandemic - Anzules-Guerra, Jazmín (2022)
Introduction: The Burnout Syndrome is characterized by depersonalization, emotional exhaustion and low personal fulfillment, it occurs in doctors who, due to their role, are exposed to chronic stress and the pandemic has not been the exception, countries such as Romania, Mexico, Colombia among others, have reported high prevalence of the syndrome, compared to the period before the pandemic. The present study aimed to characterize resident physicians with Burnout during the COVID-19 pandemic. Methods: A descriptive, observational and cross-sectional study was carried out with 40 resident doctors of the Provincial Hospital of Portoviejo, Manabí, Ecuador. Applying the MBI-HSS with its three dimensions depersonalization, emotional exhaustion and personal fulfillment. Results: Of the total population, 17 cases were obtained with high emotional exhaustion (42.5%) and depersonalization 19 cases (47.5%): with low personal fulfillment 18 (45%). Of these, 15 (37.8%) professionals met the 3 burnout criteria, mostly women (80%), average age 30.75 ± 2.30, married (60%), weekly days ≤ 72 hours (75%), with children (91.67%), work seniority ≤ 3 years (83.33%) who worked in emergencies (75%). Conclusion: During the study period, it was possible to characterize the medical population with burnout, mostly women, married, with more than one child, who work 3 days a week on duty in the emergency service, making necessary the timely identification of these cases to address it effectively and immediately.